1990
DOI: 10.1002/j.1460-2075.1990.tb08205.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuronal nicotinic acetylcholine receptor genes in the developing chick visual system.

Abstract: Expression of the neuronal non‐alpha nicotinic acetylcholine receptor (n alpha nAChR) gene is transiently stimulated in the chick optic tectum between embryonic days 7 and 16 with a peak value reached around embryonic day 12. This stimulation takes place at the time when optic nerve axons are invading this region of the brain and proceeds along a rostral to caudal gradient. Transcripts of the n alpha nAChR gene are localized in the superficial layers of the tectum at the time when cells in these layers are for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 32 publications
4
36
0
1
Order By: Relevance
“…Surgical removal of the primordial eye prior to synapse formation on embryonic chick optic tectum neurons abolishes the 10-to 15-fold transient increase in ␤2 mRNA levels normally seen in these cells (Matter et al, 1990). ␣7-nAChR expression in the neonatal rat somatosensory cortex is similarly regulated by innervation.…”
Section: Inductive Effects Of Innervation On Nachr Expressionmentioning
confidence: 92%
“…Surgical removal of the primordial eye prior to synapse formation on embryonic chick optic tectum neurons abolishes the 10-to 15-fold transient increase in ␤2 mRNA levels normally seen in these cells (Matter et al, 1990). ␣7-nAChR expression in the neonatal rat somatosensory cortex is similarly regulated by innervation.…”
Section: Inductive Effects Of Innervation On Nachr Expressionmentioning
confidence: 92%
“…Total RNA was isolated, gel-fractionated, and hybridized as described (10,15). We used as probe a 32 P-labeled ␤3 genomic fragment containing 250 bp of exon 5 (encoding amino acids Met 308 -Gln 391 ) and 240 bp of intron 5 (15).…”
Section: Methodsmentioning
confidence: 99%
“…Several nAChR subunit genes, including ␣4, ␤2, ␤3, and ␤4, are expressed in the chick retina (10), 2 and expression of ␤3 is confined to ganglion cells and amacrine neurons (15). Forsayeth and Kobrin (16) have shown that the ␤3 subunit co-assembles in vivo with the ␣4, ␤2, and ␤4 subunits to form a functional nicotinic receptor endowed with distinctive properties.…”
mentioning
confidence: 99%
“…In the chick optic tectum, however, nAChRs may also play a role in wiring of visual pathways. In this species, na (nonalpha) subunits of the nAChR are transiently expressed in the optic tectum during innervation by optic nerve fibers, whereas in "eyeless" embryos in which both optic vesicles have been removed, this transeint expression does not occur (72). This suggests that nAChR may be involved in development of the retinotectal projection in the chick embryo.…”
Section: Acetylcholine and Ocular Domi2nancementioning
confidence: 95%